Factors associated with early lung cancer mortality: a systematic review. Issue 10 (3rd October 2021) - Goussault, Helene; Gendarme, Sebastien; Assié, Jean Baptiste; Bylicki, Olivier; Chouaïd, Christos
ABSTRACT: Introduction : Despite recent therapeutic advances, lung cancer remains the primary cause of cancer deaths worldwide, and early lung mortality was poorly studied. Area covered : Early lung-cancer mortality reflects local therapy (surgery or radiotherapy) impact (localized forms), and metastatic disease evolution, comorbidities and healthcare-system accessibility. The definition of early lung cancer mortality is not consensual; thresholds range from 1 to 12 months post-diagnosis. This systematic review was undertaken to identify and analyze factors significantly associated with early lung cancer mortality. Age, male sex, non-adenocarcinoma histology, advanced stage at diagnosis and ECOG performance status are the main clinical factors of early lung cancer mortality. Active/ex-smoking also seems to favor early mortality, despite heterogeneous definitions of smoker status. For radio-chemotherapy treated locally advance disease, the early mortality rate increases according to tumor volume. Less well studied, socioeconomic characteristics (rurality and social deprivation index) yielded contradictory results, partially because definitions vary over studies. However, early lung cancer mortality is significantly higher for lower socioeconomic class patients. Expert opinion : Prospective, observational, general population studies are needed to better evaluate early lung-cancer mortality. International consensus concerning the patient-, disease- or healthcare system-linked factors of interest to be collected would facilitate comparisons among countries.